2009
DOI: 10.1258/ijsa.2009.009092
|View full text |Cite
|
Sign up to set email alerts
|

Mucocutaneous manifestations in 150 HIV-infected Indian patients and their relationship with CD4 lymphocyte counts

Abstract: Mucocutaneous findings in 150 HIV+ve cases (F, 79; M, 71) were evaluated over a one-year period. Mucocutaneous manifestations were seen in 96% with 2.9 mean number of dermatoses and mean cluster of differentiation (CD4) count of 196.33 cells/mm(3). The highest number of mean dermatoses, 3.29, was seen in individuals with severe immunosuppression. The most common mucocutaneous manifestation seen was candidiasis (35.33%), followed by seborrhoeic dermatitis (31.33%), oral pigmentation (29.33%), xerosis/ichthyosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 22 publications
8
44
1
3
Order By: Relevance
“…The co-infection of HIV with Candida may be an important exogenous factor that may influence the severity and the rate of the disease progression in HIV infected individuals [12]. In the present study, oral candidiasis (32.22%) was the most common mucocutaneous manifestation which was seen in the HIV positive persons, which collaborated with the findings of other workers (35.33%) [13]. It was reported to be 61% in another study which was done in the same institution [14] (p<0.001), whereas other workers had reported it to be 45% and 11.50% respectively [15,11].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The co-infection of HIV with Candida may be an important exogenous factor that may influence the severity and the rate of the disease progression in HIV infected individuals [12]. In the present study, oral candidiasis (32.22%) was the most common mucocutaneous manifestation which was seen in the HIV positive persons, which collaborated with the findings of other workers (35.33%) [13]. It was reported to be 61% in another study which was done in the same institution [14] (p<0.001), whereas other workers had reported it to be 45% and 11.50% respectively [15,11].…”
Section: Discussionsupporting
confidence: 88%
“…A papular pruritic eruption is a unique dermatosis which is associated with the advanced HIV infection, which is characterized by sterile papules, nodules, or pustules with a hyperpigmented, urticarial appearance and pruritis [27]. The next common manifestations were gingivitis and apathus stomatitis (4.44%) each, whereas other workers reported it to be 82.9%, 17.33% and 3% respectively [22,13,3]. Severe periodontal diseases have been associated with the alterations in the host immune system, which can predispose to gingivitis and the development of periodontitis.…”
Section: Resultsmentioning
confidence: 99%
“…Some common problems associated with HIV/AIDS are development of fever, blisters, Kaposi's sarcoma, oral warts, canker soars, oral hairy leukoplakia, gingival and periodontal diseases, thrush, swelling in salivary glands, enlarged lymph nodes, dry mouth, viral oral lesions and herpes simplex lesions etc 5,18,19 . The side eff ects of medicati ons commonly used may also aff ect the oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Some oral lesions may even Oral lesions and immunosuppression in HIV patients affect patient's quality of life [6]. Early diagnosis and appropriate treatment of oral lesions have great influence on patients' general health and can reduce the mortality rate of the disease [7]. Reduction of circulating CD4 count is the main criteria for assessing the immunosuppression status in HIV-positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patients with oral candidiasis were suffering from severe immunosuppression, and they concluded that candidiasis and gingivitis could be considered as an indicator of the disease progression [4]. The research work conducted by Sud et al and Nokta have also shown an association between low CD4 counts and candidiasis, linear gingival erythema, angular cheilitis, scabies, paronychia, oral pigmentation, diffuse hair loss and other oral symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%